1985
DOI: 10.1007/bf00327608
|View full text |Cite
|
Sign up to set email alerts
|

Doppler sonography in basilar artery occlusion

Abstract: We have investigated 6,972 patients with directional continuous-wave Doppler sonography within the last three and a half years, and have derived criteria for the sonographic diagnosis of basilar artery occlusion or tight stenosis in conjunction with 1,071 retrograde brachial angiograms. By sonographic patterns, we have suspected obstruction of the basilar artery or of both distal vertebral arteries in nine cases. Either bilateral sonographic silence or the absence of a diastolic flow component of the vertebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…17 " Recently, we demonstrated the reliability of Doppler sonography in detecting severe stenosis and occlusion of both distal vertebral arteries and/or the proximal basilar artery. 6 In this study, the correlation of directional c-w Doppler sonographic findings with the results of almost 2,000 retrograde brachial angiograms done on more than 1,500 patients indicates that the technique is also sufficient for identifying stenoses of the basilar artery with at least a 60% reduction in lumen diameter. The only prerequisites are quality recordings of the vertebral pulse curves to calculate the modified Pourcelot indices.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…17 " Recently, we demonstrated the reliability of Doppler sonography in detecting severe stenosis and occlusion of both distal vertebral arteries and/or the proximal basilar artery. 6 In this study, the correlation of directional c-w Doppler sonographic findings with the results of almost 2,000 retrograde brachial angiograms done on more than 1,500 patients indicates that the technique is also sufficient for identifying stenoses of the basilar artery with at least a 60% reduction in lumen diameter. The only prerequisites are quality recordings of the vertebral pulse curves to calculate the modified Pourcelot indices.…”
Section: Discussionmentioning
confidence: 56%
“…1 " 5 Previously, we reported the possibility of detecting a substantial increase in peripheral resistance of both distal vertebral and/or the proximal basilar arteries with Doppler pulse curves. 6 In the present study, the use of relative end-diastolic flow velocities of the vertebral arteries as circulatory resistance indices allowed, in comparison with age-matched controls, the sonographic detection of stenotic lesions of at least 60% reduction in lumen diameter in the vertebro-basilar system distal to the point of insonation. …”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Although conventional angiography remains the reference standard for assessing the vertebrobasilar circulation, it is invasive and reserved for patients for whom there is a strong neurologic indication. Although previous studies have shown a correlation between Doppler ultrasonography of the VAs and angiographic findings, 1,3,4 to our knowledge, ours is the largest to investigate the correlation between a single Doppler waveform of the V2 segment of the VA and correlative neuroimaging in an unselected patient population referred for CDU. Because of the differing modes of neuroimaging we used as the comparator studies (CTA, MRA, and angiography), calculation of the sensitivity or specificity of a single VA waveform to detect vertebrobasilar disease was not performed.…”
Section: Discussionmentioning
confidence: 92%
“…Complete evaluation of the VAs with CDU is limited by its intraforaminal course with considerable acoustic shadowing and dropout of the Doppler signal. Based on the Intersocietal Commission for the Accreditation of Vascular Laboratories standards for extracranial cerebrovascular testing, in addition to the evaluation of the common, internal, and external carotid arteries, bilateral VAs are identified and, at minimum, a single midartery Doppler signal is obtained for each cervical VA. 2 Although an HR Doppler signal in the cervical VA may indicate disease located cephalad to the ultrasound probe, ultrasonographic-angiographic correlation studies have been limited by small numbers of angiographic correlations 1,3 or by preselection of patients with neurologic symptoms. 4 Thus, the clinical importance of an HR pulsed Doppler VA waveform in an unselected patient population presenting for routine carotid ultrasonography remains uncertain.…”
mentioning
confidence: 99%